The Effect of Task-Based Learning on The Listening Skills of Second Semester Students in The English Education Study Program - Yufiriani Lase; Sahlan Tampubolon; Harpen Silitonga (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study examines the effect of Task-based Learning on students' listening skills in English as a Foreign Language learning. The research used a quantitative experimental design involving two groups of second semester students in the English Education Study Program at the University of HKBP Nommensen. Listening skills were measured through pre-tests and post-tests consisting of 25 multiple-choice questions designed to assess students’ ability to identify main ideas, specific information, and draw inferences from audio texts. The experimental group received treatment through Task-Based Learning activities, including task cycles, group discussions, and reporting stages, while the control group was taught using conventional methods. The results showed a significant improvement in the post-test scores of the experimental group, with the average increasing from 57.80 to 70.19. Meanwhile, the control group's scores increased moderately from 55.2 to 63.2. Statistical analysis using an independent t-test indicated that the obtained t-value (4.512) exceeded the critical t-table value (2.005) at a 0.05 significance level, indicating a statistically significant effect of Task-based Learning on students’ listening comprehension. These findings support using Task-based Learning as an effective instructional strategy to improve listening skills in higher education. The study recommends integrating Task-based Learning into listening instruction to enhance student engagement, comprehension, and contextual language use